Collective removal of phenol and ammonia in a moving bed biofilm reactor using modified bio-carriers: Process optimization and kinetic study - Swain G.; Sonwani R.K.; Giri B.S.; Singh R.S.; Jaiswal R.P.; Rai B.N. (My University, 2025)
The performance of a moving bed biofilm reactor (MBBR) with bio-carriers made of polypropylene-polyurethane foam (PP-PUF) was evaluated for the collective removal of phenol and ammonia. Three independent variables, including pH (5.0–8.0), retention time (2.0–12.0 h), and airflow rate (0.8–3.5 L/min) were optimized using central composite design (CCD) of response surface methodology (RSM). The maximum removal of phenol and ammonia was obtained to be 92.6, and 91.8%, respectively, in addition to the removal of 72.3% in the chemical oxygen demand (COD) level at optimum conditions. First-order and second-order kinetic models were analyzed to evaluate the pollutants removal kinetics in a MBBR. Finally, a second-order model was found to be appropriate for predicting reaction kinetics. The values of second-order rate constants were obtained to be 2.35, 0.25, and 1.85 L2/gVSS gCOD h for phenol, COD, and ammonia removal, respectively. © 2020 Elsevier Ltd